MODELS OF NATIONAL-GENDER SPACE IN RUSSIAN AND UZBEK PROSE: TYPOLOGY AND ARTISTIC REPRESENTATION - Otabek Jumayev (International Journal of Literature and Language Studies, 2026)
The article examines models of national-gender space in Russian and Uzbek prose from a comparative typological perspective. Particular attention is paid to the artistic representation of gender roles shaped by national cultural traditions and historical development. Based on the analysis of Russian and Uzbek literary works, both common and distinctive features of national-gender models are identified. The study reveals that Russian prose is primarily focused on the inner world of the individual and personal identity, whereas Uzbek prose emphasizes family values and collective responsibility. The findings contribute to a broader understanding of national-gender space as an important component of the artistic worldview.